Technical inefficiency of wheat production in some selected areas of Bangladesh - Hasan, M Kamrul; Islam, SM Fakhrul (Bangladesh Journal of Agricultural Research, 2010)
The main objective of the study was to identify and analyze the inefficiency and yield gaps of wheat production in Bangladesh. The study employed farm level cross sectional data from three major wheat growing areas of Bangladesh. Yield of wheat was found to vary across locations and farm categories. The average technical inefficiency of wheat production in Bangladesh is 16. This indicates a good potential for increasing wheat output by 16 percent with the existing technology and levels of inputs. Education and training on wheat of the farm operators was found to have significant effect on yield and technical efficiency of wheat production. Keywords: Technical inefficiency; wheat production; yield gaps. DOI: 10.3329/bjar.v35i1.5871 Bangladesh J. Agril. Res. 35(1) : 101-112, March 2010